Strategi Efektif Dalam Implementasi Sistem Informasi Manajemen Untuk Meningkatkan Kinerja Organisasi - Rahmat Pasha Hanonangan; Muhammad Irwan Padli Nasution (CV. SINAR HOWUHOWU, 2026)
This study aims to examine effective strategies for implementing Management Information Systems (MIS) to enhance organizational performance in the digital era. Based on a review of three recent journals, this research emphasizes that the success of MIS implementation is not solely determined by technological sophistication but also by the organization’s ability to integrate human resources, managerial policies, and adequate supporting infrastructure. Properly managed MIS can strengthen operational efficiency, transparency, and accountability across organizational activities. Key influencing factors include the accuracy and timeliness of data, user competence, and adaptive policies that respond to technological advancements. Using a descriptive approach through literature study, this research identifies effective MIS implementation strategies in various organizational contexts. The findings indicate that enhancing human resource capacity, fostering a digital work culture, and reinforcing system security and integration are essential steps toward achieving superior and sustainable organizational performance amid ongoing digital transformation.